FRI0372 Pharmacokinetics and immunogenicity of pegloticase (PL) infused every 3 weeks to treat refractory gout (RG), including in organ transplant recipients (TR). (23rd January 2014) - Hershfield, M.S.; Ganson, N.J.; Kelly, S.J.; Scarlett, E.L.; Jaggers, D.A.; Sundy, J.S.
Abstract : Background: PL is approved for treating RG at 8 mg IV every 2 wks. Phase 1 testing suggested that 8 mg IV every 3 wks might also be effective. We have evaluated this dose in an open-label trial (Duke-3), which included some TR, an important RG subset excluded from previous trials. Objectives: 1) Assess PK of every 3 wk PL, and ability to maintain plasma urate concentration (PUA) <6 mg/dL. 2) Characterize the Ab response to PL, including epitope specificity and relationship to loss of efficacy and AE; 3) Compare immunogenicity and efficacy in TR vs NT RG patients. Methods: Duke-3 was conducted under investigator IND#11274 sponsored by the USFDA in 27 PL-naïve RG patients, including 20 NT and 7 TR (3 NT patients treated in earlier trials and known to be PL Ab+ are excluded from analysis). Prednisone (20 mg) + fexofenadine (60 mg) were given the night before, and fexofenadine + hydrocortisone (200 mg IV) the morning of each infusion. Plasma uricase activity was monitored by radiochemical-HPLC, and PUA by HPLC, before and 2 h after each infusion, then weekly through d21 after the last infusion. Following d2 after infusion #1, loss of efficacy was indicated by return of PUA to ≥6 mg/dL. Screening for IgG Ab to PL was by ELISA; specificity for uricase protein vs PEG was assessed, respectively, by the ability of un-PEGylated recombinant porcine uricase vs 10 kDa PEG to inhibit the screening ELISA. All methods were validated using USFDA guidelines. In patients completing 5 infusions, all PUA values between d2 after infusion #1 through d21 after infusion #5 were averaged; mean PUA <6 mg/dL indicated a sustained response. Results: In 26/27 patients, PUA fell from 10.8±1.3 mg/dL pretreatment, to ≤1 mg/dL by 48 h after infusion #1; one patient experienced an AE and did not complete infusion #1. Including the latter, 10/27 (37%) patients failed to maintain PUA <6 mg/dL, including 9/20 (45%) NT and 1/7 (14%) TR; all 10 developed IgG Ab to PL that was specific for PEG, not uricase protein, and caused rapid clearance of uricase activity from plasma. Titers ranged from ∼1:100 to >1:10, 000. Of interest, anti-PEG Ab was detectable in 5 of these 10 patients prior to treatment, and increased after exposure to PL. 21 patients, including 5 TR, completed all 5 infusions; 6 patients including 2 TR did not complete due to AE (details presented in a related abstract) and 5 of these 6 (4 NT, 1 TR) were anti-PEG Ab+. Among the 21 who completed, efficacy was sustained in 16 (including 4 TR), who did not develop significant anti-PEG Ab; their PUA averaged 0.9±0.5 mg/dL over the 15-wk study period. In the other 5 completers, who were anti-PEG Ab+, PUA averaged 6.6±2.1 mg/dL. PK (mean AUC and Cmax for plasma uricase activity) in the 16 completers with sustained efficacy was similar to results obtained for an 8 mg dose of PL in phase 1 testing. Conclusions: This short-term study indicates favorable PK and efficacy with 8 mg PL infused at 3 wk intervals. Detection of anti-PEG Ab prior to treatment predicted increased risk for loss of efficacy and AE. Chronic immunosuppression to prevent graft rejection may protect organ transplant recipients from developing anti-PEG Ab. Testing for anti-PEG Ab may be used to guide trials of immunosuppressive strategies to enhance the therapeutic profile of PL. Disclosure of Interest: M. Hershfield Consultant for: Savient Pharmaceuticals, N. Ganson: None Declared, S. Kelly: None Declared, E. Scarlett: None Declared, D. Jaggers: None Declared, J. Sundy Consultant for: Savient Pharmaceuticals